Phylogenomic Rhizobium Species Are Structured by a Continuum of Diversity and Genomic Clusters - González, Víctor; Santamaría, Rosa Isela; Bustos, Patricia; Pérez-Carrascal, Olga María; Vinuesa, Pablo; Juárez, Soledad; Martínez-Flores, Irma; Cevallos, Miguel Ángel; Brom, Susana; Martínez-Romero, Esperanza; Romero, David (Frontiers in Microbiology, 2019)
The bacterial genus Rhizobium comprises diverse symbiotic nitrogen-fixing species associated with the roots of plants in the Leguminosae family. Multiple genomic clusters defined by whole genome comparisons occur within Rhizobium, but their equivalence to species is controversial. In this study we investigated such genomic clusters to ascertain their significance in a species phylogeny context. Phylogenomic inferences based on complete sets of ribosomal proteins and stringent core genome markers revealed the main lineages of Rhizobium. The clades corresponding to R. etli and R. leguminosarum species show several genomic clusters with average genomic nucleotide identities (ANI > 95%), and a continuum of divergent strains respectively. They were found to be inversely correlated with the genetic distance estimated from concatenated ribosomal proteins. We uncovered evidence of a Rhizobium pangenome that was greatly expanded, both in its chromosomes and plasmids. Despite the variability of extra-chromosomal elements, our genomic comparisons revealed only a few chromid and plasmid families. The presence/absence profile of genes in the complete Rhizobium genomes agreed with the phylogenomic pattern of species divergence. Symbiotic genes were distributed according to the principal phylogenomic Rhizobium clades but did not resolve genome clusters within the clades. We distinguished some types of symbiotic plasmids within Rhizobium that displayed different rates of synonymous nucleotide substitutions in comparison to chromosomal genes. Symbiotic plasmids may have been repeatedly transferred horizontally between strains and species, in the process displacing and substituting pre-existing symbiotic plasmids. In summary, the results indicate that Rhizobium genomic clusters, as defined by whole genomic identities, might be part of a continuous process of evolutionary divergence that includes the core and the extrachromosomal elements leading to species formation